Stabilization of the U5-leader stem in the HIV-1 RNA genome affects initiation and elongation of reverse transcription - Beerens, Nancy (Oxford University Press, 2000)
Reverse transcription of the Human Immunodeficiency Virus type I (HIV-1) RNA genome is primed by a cellular tRNA–lys3 molecule that binds to the primer binding site (PBS). The PBS is predicted to be part of an extended RNA structure, consisting of a small U5-PBS hairpin and a large U5-leader stem. In this study we stabilized the U5-leader stem of HIV-1 to study its role in reverse transcription. We tested in vitro synthesized wild-type and mutant templates in primer annealing, initiation and elongation assays. Stabilization of the stem inhibits the initiation of reverse transcription, but not the annealing of the tRNA primer onto the PBS. These results suggest that stabilization of the stem results in occlusion of a sequence motif that is involved in an additional interaction with the tRNA–lys3 primer and that is needed to trigger the initiation of reverse transcription. The stable structure was also found to affect the elongation of reverse transcription, causing the RT enzyme to pause upon copying 7–8 bases into the extended base paired stem. The stabilizing mutations were also introduced into proviral constructs for replication studies, demonstrating that the mutant viruses have a reduced replication capacity. Analysis of a revertant virus demonstrated that opening of the stabilized U5-leader stem can restore both virus replication and reverse transcription.